Improvement ecological and effective indicators of diesel in operation by recirculation leaks in the fuel equipment - Y. P. Makushev; A. L. Ivanov; V. A. Kania; S. S. Voytenkov (Вестник СибАДИ, 2017)
Theoretical and experimental investigation of diesel power system with recirculating fuel leaks have been held. Method of calculating fuel leaks depending on the wear of spray nozzles is shown. The ability to preserve the stability of diesel fuel equipment parameters during continuous operation has been proved. The test results of the fuel equipment with nozzles having a closed volume above the needle are given. The authors noted an increase stability of the experimental fuel equipment parameters, reducing specific fuel consumption and smoke exhaust gas.